ISLAMIC EDUCATION AND SCHOOL WELL-BEING FOR ADOLESCENTS DURING THE COVID-19 PANDEMIC - Abdillah, Hafizh Zain; Madjid, Abd. (JURNAL RISET PENDIDIKAN DAN PENGAJARAN, 2024)
This article aims to explore the impact of Islamic education on the well-being of adolescents amidst the Covid-19 pandemic. The main focus is to shed light on how Islamic education can enhance school well-being for adolescents during these challenging times. The methodology employed in this article involves a comprehensive literature review. The findings highlight the positive effect of Islamic education in boosting the well-being of adolescents in the midst of the Covid-19 pandemic. It is crucial to emphasize the importance of implementing Islamic education to elevate students' school well-being. The implications of this study are anticipated to offer valuable insights for the advancement of Islamic education, particularly in the realm of Islamic psychology, as a viable solution to enhance school well-being among adolescents during the Covid-19 pandemic.